Quick Automatic Synthesis of Solvent-Free 16α-[18F] Fluoroestradiol: Comparison of Kryptofix 222 and Tetrabutylammonium Bicarbonate - Jiang, Xiao; Li, Yingchun; Wang, Xiaoxiong; Shen, Taipeng; Li, Xiuli; Yao, Yutang; Zhang, Ge; Kou, Ying; Shen, Jiaqi; Luo, Zhifu; Cheng, Zhuzhong (Frontiers in Oncology, 2020)
ER expression level of human breast cancer often reflects the stage of disease and is usually monitored by immunohistochemical staining in vitro. The preferable non-invasive and real-time diagnosis in vivo is more accessible by PET scan using 16α-[18F]FES. The objective of this study was to develop a quick automatic method for synthesis of solvent free 16α-[18F]FES using a CFN-MPS-200 synthesis system and compare the catalytic efficiency of two phase transfer catalysts Kryptofix 222/K2CO3 (K222/K2CO3) and tetrabutylammonium hydrogen carbonate (TBA•HCO3). In this method, phase transfer catalysts K222/K2CO3 and TBA•HCO3 were used respectively. The intermediate products were both hydrolyzed with hydrochloric acid and neutralized with sodium bicarbonate. The crude product was purified with semi-preparative HPLC and the solvent was removed by rotary evaporation. The effects of radiofluorination temperature and time on the synthesis were also investigated. Radiochemical purity of solvent-free product was above 99% and the decay-corrected radiochemical yield of 16α-[18F]FES was obtained in 48.7±0.95% (catalyzed by K222/K2CO3, n=4) and 46.7±0.77% (catalyzed by TBA•HCO3, n=4, respectively). The solvent free 16α-[18F]FES was studied in clinical diagnosed breast cancer patients, and FES-PET results were compared with pathology diagnosis results to validate the diagnosis value of 16α-[18F]FES. The new method was more reliable, efficient and time-saving. There was no significant difference in catalytic activity between K222/K2CO3 and TBA•HCO3.